2016
DOI: 10.3390/rel7120136
|View full text |Cite
|
Sign up to set email alerts
|

Trust at Work: A Study on Faith and Trust of Protestant Entrepreneurs in China

Abstract: There is much talk about the trust crisis in China and the possible role of religion in rebuilding China's moral order. This study is an attempt to examine religion's impact on the emerging market economy in China, focusing on trust in business relations that might be generated by the Christian faith. Based on 43 in-depth interviews with Christian entrepreneurs in China, our study shows that the majority of our respondents tend to be: (1) more willing to be trustworthy after becoming Christians; (2) trusting p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Such works include Confucian social model (Li and Liang 2015), Confucian Ren-Yi Wisdom (Zhu 2015) and Zhong-yong thinking (Ma, Gu, and Liu 2017). Intriguing studies have also introduced religion and faith into contextualization such as faith and trust of protestant (Guo and Miller 2010); moral sentiment (Yiu et al 2014b); Confucian social model (Li and Liang 2015); relational and institutional embeddedness (Avgerou and Li 2013); Confucian Ren-Yi Wisdom (Zhu 2015); religious and political involvement (Du 2017); prominent business association (Ma, Rui, and Wu 2015); reconfiguration of gender hierarchies (Wallis 2015); Zhong-yong thinking (Ma, Gu, and Liu 2017); mentoring (Ting, Feng, and entrepreneurs (Tong and Yang 2016) and religious and political involvement (Du 2017). Research has also touched upon the contexts of cultural values regarding embeddedness and gender such as relational and institutional embeddedness (Avgerou and Li 2013) and reconfiguration of gender hierarchies (Wallis 2015).…”
Section: An Overview Of Approaches To Contextualization In Chinese Entrepreneurship Researchmentioning
confidence: 99%
“…Such works include Confucian social model (Li and Liang 2015), Confucian Ren-Yi Wisdom (Zhu 2015) and Zhong-yong thinking (Ma, Gu, and Liu 2017). Intriguing studies have also introduced religion and faith into contextualization such as faith and trust of protestant (Guo and Miller 2010); moral sentiment (Yiu et al 2014b); Confucian social model (Li and Liang 2015); relational and institutional embeddedness (Avgerou and Li 2013); Confucian Ren-Yi Wisdom (Zhu 2015); religious and political involvement (Du 2017); prominent business association (Ma, Rui, and Wu 2015); reconfiguration of gender hierarchies (Wallis 2015); Zhong-yong thinking (Ma, Gu, and Liu 2017); mentoring (Ting, Feng, and entrepreneurs (Tong and Yang 2016) and religious and political involvement (Du 2017). Research has also touched upon the contexts of cultural values regarding embeddedness and gender such as relational and institutional embeddedness (Avgerou and Li 2013) and reconfiguration of gender hierarchies (Wallis 2015).…”
Section: An Overview Of Approaches To Contextualization In Chinese Entrepreneurship Researchmentioning
confidence: 99%
“…In a study by Tong (2012) on overseas Chinese Christian businesspeople in Shanghai, personal piety was found serve as the foundation of business ethics and guide their dealings with Chinese officials, clients, business partners, and ordinary workers. In their study on trust among Protestant entrepreneurs, Tong and Yang (2016) found that Chinese Protestant entrepreneurs wanted to be more trustworthy and to be more trustful of others, after becoming Christians, and some of them thought that a major religion like Christianity would lead to better moral behavior.…”
Section: Spirituality and Religion In The Workplace: An Overviewmentioning
confidence: 99%
“…A Christian's ability to inspire trust (cf. Tong and Yang 2016) in others is good not only for sealing business deals but also for motivating workers and establishing collegial atmosphere in the workplace. When asked how important religious faith is in the workplace, Simon opines: It's very important.…”
Section: Being Christians In the Workplace: Employees Of A "Different Kind"mentioning
confidence: 99%
“…In a study by Tong (2012) on overseas Chinese Christian businesspeople in Shanghai, personal piety was found serve as the foundation of business ethics and guide their dealings with Chinese officials, clients, business partners, and ordinary workers. In their study on trust among Protestant entrepreneurs, Tong and Yang (2016) found that Chinese Protestant entrepreneurs wanted to be more trustworthy and to be more trustful of others, after becoming Christians, and some of them thought that a major religion like Christianity would lead to better moral behavior.…”
Section: Spirituality and Religion In The Workplace: An Overviewmentioning
confidence: 99%
“…A Christian's ability to inspire trust (cf. Tong and Yang 2016) in others is good not only for sealing business deals but also for motivating workers and establishing collegial atmosphere in the workplace. When asked how important religious faith is in the workplace, Simon opines:…”
Section: Being Christians In the Workplace: Employees Of A "Differentmentioning
confidence: 99%